2005
DOI: 10.1177/1012690205057191
|View full text |Cite
|
Sign up to set email alerts
|

Stratification Patterns of Active Sport Involvement Among Adults

Abstract: This study examines leisure-time sport participation among adults according to their socio-cultural background and from a time-trend perspective. Using stapled cross-sectional survey data, sport participation trends in Flanders (Belgium) are studied for the 1979-99 period. The study explores the extent to which social inequalities in leisure-time sport still prevail. The results indicate that age, gender and social class remain the most important factors influencing sport involvement. Differences according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 9 publications
(7 reference statements)
7
70
1
3
Order By: Relevance
“…Moreover, the results are congruent with those from previous national and regional studies into sport participation which have shown that in many European countries physical activity patterns are still characterised by social differences (see Collins & Kay, 2003;Lamprecht & Stamm, 1995;Scheerder et al, 2002;Scheerder, Vanreusel, & Taks, 2005).…”
Section: The Above Results Imply That the Full Democratisation Of Sposupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, the results are congruent with those from previous national and regional studies into sport participation which have shown that in many European countries physical activity patterns are still characterised by social differences (see Collins & Kay, 2003;Lamprecht & Stamm, 1995;Scheerder et al, 2002;Scheerder, Vanreusel, & Taks, 2005).…”
Section: The Above Results Imply That the Full Democratisation Of Sposupporting
confidence: 81%
“…Sport participation studies generally refute the idea that sport has become more democratic and egalitarian. Empirical research on a national level has revealed that participation in sport activities still reflects the social positions and social stratification patterns that exist in society (see Collins & Kay, 2003;Lamprecht & Stamm, 1995;Scheerder et al, 2002;Scheerder, Vanreusel, & Taks, 2005). These social differences can be summarised as follows: (1) more men than women take part in sport, (2) sport participation is proportional related to age-increasing age, decreasing sport participation, (3) there is a higher percentage of sport participants in groups with a higher socio-economic status (education, profession, income level), and (4) individuals living in (large) towns take part more in sport than those living in villages.…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic Status (SES), has a profound influence on sport and physical activity. Previous findings show that living in low SES areas is predictive of low levels of participation in sport and physical activity [5][6][7][8][9][10][11][12][13][14][15] . Only male participants took part in the present study.…”
Section: General Informationmentioning
confidence: 99%
“…A period effect takes place at the same time for all generations or phases of the life cycle (Pilgaard, 2013: 37). An economic crisis, the universalization of the education system or a boom in discourse the benefits of sports for health are all circumstances that may produce a period effect in sporting practice (Hirvensalo, Lampinen and Rantanen, 1998;Scheerder, Vanreusel and Taks, 2005;Breuer and Wicker, 2009).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%